2019
DOI: 10.5993/ajhb.43.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Alcohol Use Behaviors among Homeless Men and Women

Abstract: Objectives: This study characterized alcohol use behaviors by sex among sheltered homeless adults and explored associations with health and readiness to change drinking behaviors. Methods: Participants (N=581; 63.7% men; Mage=43.6, 29.4% White) self-reported alcohol use and readiness to change drinking behaviors. Sex differences were analyzed via Wilcoxon rank-sum, Chi-Square tests, logistic regression, and ANCOVAs. Results: Overall, 38.5% of the sample met criteria for current at-risk drinking, 39.7% self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…A recent Oklahoma City–based outreach survey found that 39.7% of homeless individuals self-reported a history of alcohol problems, and a Toronto-based survey showed that 27% of the homeless population reported recent cocaine use. 10 , 11…”
Section: Introductionmentioning
confidence: 99%
“…A recent Oklahoma City–based outreach survey found that 39.7% of homeless individuals self-reported a history of alcohol problems, and a Toronto-based survey showed that 27% of the homeless population reported recent cocaine use. 10 , 11…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who are homeless face numerous challenges to maintain or improve their health, and as a result suffer disproportionate rates of morbidity and mortality [2][3][4]. Two prevalent health risk factors among homeless adults include food insecurity, which is the inability to acquire adequate nutritious food due to insufficient money or other means to enable sufficient food access [5,6], and alcohol use problems [7]. Although these constructs have been shown to be associated among domiciled samples [8][9][10][11][12], their association among homeless samples has not been extensively researched.…”
Section: Introductionmentioning
confidence: 99%
“…Problematic alcohol use, including heavy alcohol use and alcohol dependency/abuse, are about 10 times more prevalent among homeless individuals than their domiciled counterparts [23][24][25]. Studies indicate alcohol dependence disorder rates of 8.1% to 58.5% [23], and at-risk drinking rates from 31% to 39% [7,26]. The lifetime prevalence of alcohol use disorders is about 60%, and the current prevalence rate is about 40%, among individuals who are homeless [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous research among domiciled populations has shown that women were more likely than men to rate their health as poor, which may lead to more frequent utilization of hospital care [38]. Further, homeless women have higher rates of severe mental illness and chronic medical illness, and similar rates of alcohol use behaviors when compared to homeless men [3,4,15,39]. Homeless women also lack access to preventive care such as prenatal care [40], mammograms, and Pap tests [41] and experience sexual assault at higher rates than homeless men [42], which may lead to increased need for emergency treatment.…”
Section: Discussionmentioning
confidence: 99%